Время серебра: [стихи : сборник] / Анатолий Демьянов - Демьянов Анатолий Илларионович (Удмуртия, 2018)
Экземпляры: ф.18 (20200921) / Инвентарный номер: 3531 / Цена: / Сис.шифр: 84(2Рос=Рус)6-5 / Авт.знак: Д 32 / ГРНТИ: 17.82.10 / ББК: 84(2Рос=Рус)6-5